A methodology for the removal of area bonded fibre laminates from paper-based objects at the National Library of Scotland. Issue 3 (2nd September 2019) - Griffin ACR, Isobel; O'Regan, Anna
Abstract: Lamination is a conservation treatment used to strengthen fragile paper objects by mending tears and losses and providing reinforcement—thereby facilitating handling—and to protect objects from deterioration due to environmental factors. Over the course of time, conservators have used various materials for lamination, including silk, cellulose acetate and heat-set tissues, such as area bonded fibre (ABF). ABF was applied extensively to maps, printed books and manuscripts in the National Library of Scotland (the Library) in the 1970s and 1980s, and anecdotal evidence suggests it was also used in some of the other larger libraries and archives in the UK and Europe. However, by the end of the twentieth century it had fallen out of favour as concerns grew over whether the treatment was appropriate, fuelled by visible evidence that ABF deteriorated as it aged. This paper describes a research project aimed at developing a quick and efficient method of removing ABF from documents and maps at the Library. It was found that removal of ABF with mechanical methods only is not feasible and that the use of an organic solvent is required, with acetone proving the most effective. For economic and health and safety reasons, it would be preferable to use acetone in small and controlled quantities, for example in a gel or for blotter washing, but this slows down the treatment and increases the risk that the media will shift or paper fibres will be removed, making immersion washing the safest option in general, particularly for large format items.